Eritrocinesis en policitemia vera - Varela, J. E.; Etcheverry, M. A.; Capalbo, Elmo Eduardo; Bomchil, Guillermo (Unión Panamericana. Organización de los Estados Americanos; Estados Unidos, 1960)
Fil: Varela, J. E. Comisión Nacional de Energía Atómica; Argentina